Pyrogallol acts as a novel anticancer factor to enhance the sensitivity to cisplatin in ovarian cancer cells through inducing miR-15a upregulation - Azin Shirani; Razieh Mirabbasi; Leila Shabani; Somayeh Reiisi (Egyptian Journal of Medical Human Genetics)
Abstract Introduction Pyrogallol is a catechin compound, as an active ingredient extracted from Emblica officinalis, has antiproliferative and antiapoptotic effects on some of the human cancer cells. Cisplatin is known as an effective chemotherapeutic agent against cancer by inducing DNA damage and apoptosis. However, the effect of pyrogallol alone and in combination with cisplatin on proliferation and apoptosis of ovarian cancer has not yet been reported. Methods In the present study, ovarian carcinoma cell line A2780 was cultivated, and the anticancer properties of pyrogallol and cisplatin determined by cell treatment of the two drugs separately and combination. Cell viability and apoptosis rate was investigated by MTT assay and flow cytometry. The effects of the compounds in inhibiting colony formation and migration were measured by colony formation and scratch methods. Results The results of the present study revealed that pyrogallol significantly inhibited the proliferation of A2780 cells in a dose-dependent manner. The combination treatment of pyrogallol and cisplatin exhibited a prominent inhibitory effect on the growth, colony formation and migration, and increased the induction of apoptosis up to 2.5 times compared to single treatments. Also, the qPCR results showed a significant increase in the expression of miR-15a and a decrease in the expression of miRNA target genes under treatment with the drugs both separately and in their combination. Conclusion This study suggests that the combination treatment of pyrogallol and cisplatin significantly increases the death of ovarian cancer cells by inducing apoptosis. Therefore, it can boost the efficacy of chemotherapy and reduce its side effects. It is hoped that the findings of the present study can provide a new perspective for pyrogallol as a therapeutic agent in the treatment of ovarian cancer.